Influence of corneal thickness on intraocular pressure measurements following Descemet's stripping automated endothelial keratoplasty (DSAEK) - Klamann, M K J; Maier, A-K B; Gonnermann, J; Torun, N; Ruokonen, P C (Der Ophthalmologe : Zeitschrift der Deutschen Ophthalmologischen Gesellschaft, 2012)
The aim of this study was to evaluate the effect of increased corneal thickness after Descemet's stripping automated endothelial keratoplasty (DSAEK) on intraocular pressure (IOP) measured by four different techniques. In this study 30 eyes from 30 patients with successful DSAEK treatment (group 1) and 30 eyes of 30 healthy subjects (group 2) were enrolled. The IOP was measured with iCare, IOPen, Goldmann applanation tonometry (GAT) and dynamic contour tonometry (DCT) techniques. Central corneal thickness (CCT) was measured by ultrasonic pachymetry. These data were used for statistical analysis. The mean IOP measured by GAT, DCT, iCare and IOPen was 13.2, 16.1, 12.5 and 14.2 mmHg in group 1 and 13.4, 14.4, 14.4 and 13.3 mmHg in group 2, respectively. Correlations between IOP and CCT were not statistically significant in either group. The results of IOP measurements by the iCare, IOPen, GAT and DCT techniques seem to be unrelated to artificially thickened corneas after DSAEK. In spite of partially good correlation between the four techniques a direct exchange of the devices is not recommended on account of the wide dispersion of values.